If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) = 3(x + 3) Reorder the terms: 3(-3 + x) = 3(x + 3) (-3 * 3 + x * 3) = 3(x + 3) (-9 + 3x) = 3(x + 3) Reorder the terms: -9 + 3x = 3(3 + x) -9 + 3x = (3 * 3 + x * 3) -9 + 3x = (9 + 3x) Add '-3x' to each side of the equation. -9 + 3x + -3x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 0 = 9 + 3x + -3x -9 = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 = 9 + 0 -9 = 9 Solving -9 = 9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| g+15-4g-6g= | | m*9-1=-2 | | v+v-33.4+v+24.1=189.9 | | -3x-4+3x=-4 | | 3w^2-14w-5=0 | | -10=10(k+9) | | v=(v-31.4) | | 2z-8=4 | | -22x-22=128+3x | | 4-6a+7=-11 | | 10+6c=52 | | 2x+25=3x-13-x | | 7x-6+8x=19 | | 9w-4=77 | | -6x^2+11x+10=0 | | -8p+3=29 | | 3x+5x-5+9-2x= | | 2ax+3y=13 | | 3m^2+12m+7=0 | | 2x-8=6x+12 | | X^2+2x-600=0 | | 2x-8=6x+13 | | 3a^2+11ab-4b^2= | | -2x+3+3x-9= | | v+27.4=194.9 | | 7-(3x+2)=2x-11+3x | | -2+3+3x-9= | | v-30.1+v+27.4=194.9 | | v+v-30.1+v+27.4=194.9 | | 3y-12=21 | | 4x-7=8x+21 | | 7m-2n=2 |